20-Hydroxyecdysone Boosts Energy Production and Biosynthetic Processes in Non-Transformed Mouse Cells - Oleg Shuvalov; Yulia Kirdeeva; Elizaveta Fefilova; Alexandra Daks; Olga Fedorova; Sergey Parfenyev; Alexander Nazarov; Yulia Vlasova; George S. Krasnov; Nick A. Barlev (MDPI AG, 2024)
20-Hydroxyecdysone (20E) is an arthropod steroid hormone that possesses a number of beneficial pharmacological activities in humans, including anabolic, antioxidant, hypoglycemic, cardioprotective, hepatoprotective, neuroprotective, and antineoplastic properties, etc. While several studies have explored the anabolic activity of 20E in muscle cells, they have concentrated on its effects on myofibril size, protein biosynthesis intensity, and myostatin expression, without assessing energy metabolism. In this research, we have demonstrated that 20E boosts both catabolism and anabolism, coupling energy-producing and biosynthetic metabolic processes in mouse myoblasts and fibroblasts in the same way. Using a transcriptomic approach, we identified the 20E-mediated up-regulation of genes involved in different metabolic processes. Further experiments revealed that 20E increased the levels of enzymes involved in glycolysis and one-carbon metabolism. It also increased the uptake of glucose, glycolysis, respiration, the production of ATP, and global protein biosynthesis in mouse myoblasts and fibroblasts. This phenomenon involves the PI3K/AKT/mTOR signaling pathway. Taken together, the observed 20E-dependent upregulation of energy metabolism may be the main reason for 20E's well-known anabolic activity.